Writers' mistakes a handbook of common blunders and ways to mend them - Olmsted, Franklin B. (Lanham, MD Rowman & Littlefield, 2024)
"Writers Mistakes: A Handbook of Common Blunders and Ways to Mend Them is a comprehensive guide where readers will find hints on how to avoid certain words, phrases, and common mistakes that can obscure the messages of ones work"-- Provided by publisher.
Ill chosen words -- Needless words -- Awkward sentences -- Problematic paragraphs -- Common grammatical mistakes.
Includes bibliographical references and index.
Keywords: Authorship -- Technique -- Handbooks, manuals, etc; English language -- Grammar -- Handbooks, manuals, etc; English language -- Rhetoric -- Handbooks, manuals, etc